Is atomic carbon a good tracer of molecular gas in metal-poor galaxies? - Glover, Simon; Clark, Paul C. (Monthly notices of the Royal Astronomical Society, 2016)
Carbon monoxide (CO) is widely used as a tracer of molecular hydrogen (H2) in metal-rich galaxies, but is known to become - ineffective in low-metallicity dwarf galaxies. Atomic carbon has been suggested as a superior tracer of H2 in these metal-poor systems, but its suitability remains unproven. To help us to assess how well atomic carbon traces H2 at low metallicity, we have performed a series of numerical simulations of turbulent molecular clouds that cover a wide range of different metallicities. Our - simulations demonstrate that in star-forming clouds, the conversion factor between [C I] emission and H2 mass, XCI, scales approximately as XCI ∝ Z-1. We recover a similar scaling for the CO-to-H2 conversion factor, XCO, but find that at this point in the evolution of the clouds, XCO is consistently smaller than XCI, by a factor of a few or more. We have also examined how XCI and XCO evolve with time. We find that XCI does not vary strongly with time, demonstrating that atomic carbon remains a good tracer of H2 in metal-poor systems even at times - significantly before the onset of star formation. On the other hand, XCO varies very strongly with time in metal-poor clouds, showing that CO does not trace H2 well in starless clouds at low metallicity.
Gesehen am 19.06.2020